MEDIA PEMBELAJARAN VISUAL SEJARAH KEBUDAYAAN ISLAM DALAM MENINGKAT MINAT BELAJAR SISWA MADRASAH - Musliaty, Musliaty (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2018)
The general objective of this study was to determine the increased interest of learning in VIII grade MTI SKI in Cilellang DDI through the use of visual learning media. This type of research is quantitative descriptive research carried out at MTs DDI Cilellang. The main instrument in this study was a questionnaire that was supported by observation guideline instruments and documentation format. The study population was 30 people. While the sample amounted to 30 people. Data collection techniques were observation, questionnaire, and documentation. Data analysis techniques were editing, scoring, and analysis. The results of the study showed that visual learning media was effective in increasing SKI learning interest in class VIII students of Cilellang MTI DDI. Thus the hypotheses that have been proposed are proven, namely the use of visual learning media in the history of Islamic culture can increase the interest in learning class VIII Madrasah Tsanawiyah DDI Cilellang in Barru Regency.